STRATEGI PROMOSI PT MUSICA STUDIO'S DENGAN INTERNET DALAM MEMPROMOSIKAN KARYA LAGU BARU - Yulia Citra; Gita Widiasanty (Jurnal Cakrawala Ilmiah, 2026)
The music industry is a type of business that markets services to consumers. As time progresses in human life, music has become a culture with the emergence of new music genres. Record companies serve as a means for artists or musicians to promote and produce their musical works, making record companies the most important part and a barometer for the development of music in terms of technology, creativity, productivity, and musical freedom. PT. Musica Studio is one of the largest recording companies in Indonesia, founded in 1970, and has produced many recordings to this day. PT. Musica Studio's enhances its promotional strategy by keeping up with the times through internet strategies to promote new song works. This research aims to describe PT Musica Studio's promotional strategies using the internet to promote new song works. The theory used is internet marketing with a primary focus on Content Marketing, Mobile Marketing, Continuous Marketing, Integrated Digital Marketing, and Visual Marketing. This research method uses a constructivist paradigm, with a qualitative approach and descriptive nature, by conducting interviews with key informants, internal supporting informants and external supporting informants. This research describes the promotional strategies using the internet employed by PT Musica Studio's in promoting new song works. The results of this study indicate that the internet marketing strategy has been successfully implemented by PT Musica Studio's, allowing the new songs to be effectively promoted.